An Evaluation Of The Electrical Protection Installation System At PT. BTP Class 1 Medan North Part - Solly Aryza; Iskandar Iskandar; Muhammad Bintang Ramadhan; Bernike Patresia Sitepu (Jurnal Scientia, 2024)
The continuous advancement of technology over the years has led to the sophistication of various facilities, including lighting systems. Lighting is essential in every corporate setting, illuminating spaces to facilitate activities and enhance visibility. It plays a crucial role in activity planning to achieve specific goals. The quality of lighting in a room is determined by factors such as intensity and suitability for different types of tasks. Research has been conducted on space lighting intensity using the SNI Standard 16-7062-2004, along with calculations of the electrical energy consumption. Light intensity measurements are taken using a Lux Meter during field observations. Rooms are designed to meet standard health requirements for office and industrial environments, ensuring adequate Illumination Intensity (E) to support various activities. Tests are conducted to determine the appropriate lighting fixtures for each room, with the primary goal of ensuring that employees can work safely and comfortably in their work environment.